Digital Track Map for the VEXA expert system - Adam Hlubuček (Acta Polytechnica CTU Proceedings)
This paper aims to summarize possible solutions of a Digital Track Map proposal, designed to become a data source for the VEXA decision-making system. The VEXA project is carried out in cooperation of the Department of Applied Mathematics at the Czech Technical University in Prague – Faculty of Transportation Sciences and the AŽD Praha s. r. o. company. The Digital Track Map is an indispensable data source describing the railway line intended for the VEXA supervised trains operation and its surroundings. Being created in the ArcGIS Pro software environment, the digital map allows individual objects to be visualized and handled as standard GIS features and described by related data stored in a geodatabase. Depending on the object class, the object location can be expressed in different ways. Not only physical location (directly expressible using GIS features) but also functional location (as the objects relate to a particular track) must be considered.